A rare presentation of Kikuchi Disease with Hemolytic Uremic Syndrome - Khan, Salwa Tauseeq (Pak J Med Sci, 2019)
Kikuchi disease (KD) or also known as Kikuchi Fujimoto disease is named after scientists Kikuchi and Fujimoto who describe the disease in Japan in 1972. KD originally reported from Asia but later case reports from different regions of world have been published. It is a benign condition of necrotizing histiocytic lymphadenitis which mimic like Lymphoma, diagnosis of KD is based on histo-pathological findings from lymphnodes. It is a rare condition and mostly case reports have been published, it can have an association with other pathologies. We aim to report a case where KD has been found in a young woman in association with hemolytic uremic syndrome and acute kidney injury.